Long-term responses to treatment in UK veterans with military-related PTSD: an observational study. Issue 9 (16th September 2016) - Murphy, Dominic; Spencer-Harper, Lucy; Carson, Carron; Palmer, Emily; Hill, Kate; Sorfleet, Nicola; Wessely, Simon; Busuttil, Walter
Abstract : Objectives: Military-related trauma can be difficult to treat. Evaluating longer term responses to treatment and identifying which individuals may need additional support could inform clinical practice. We assessed 1-year outcomes in UK veterans treated for post-traumatic stress disorder (PTSD). Design: Within-participant design. Setting: The intervention was offered by Combat Stress, a mental health charity for veterans in the UK. Participants: The sample included 401 veterans who completed a standardised 6-week residential treatment. Of these, 268 (67%) were successfully followed up a year after the end of treatment. Methods: A range of health outcomes were collected pretreatment and repeated at standard intervals post-treatment. The primary outcome was severity of PTSD symptoms, and secondary outcomes included measures of other mental health difficulties (depression, anxiety and anger), problems with alcohol, and social and occupational functioning. Results: Significant reductions in PTSD severity were observed a year after treatment (PSS-I: −11.9, 95% CI −13.1 to −10.7). Reductions in the secondary outcomes were also reported. Higher levels of post-treatment functional impairment (0.24, 95% CI 0.08 to 0.41) and alcohol problems (0.18, 95% CI 0.03 to 0.32) were associated with poorer PTSD treatment response at 12 months. Conclusions: This uncontrolled study suggests the longer term benefits of a structured programme to treat UK veterans with PTSD. Our findings point to the importance of continued support targeted for particular individuals post-treatment to improve longer term outcomes.